FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA UKM DI KOTA BANDA ACEH - Zuhra, Rahmi; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aimed to examine the influence of computer self-efficacy, non-physical work environment, level of education, and accounting knowledge on the effectiveness of the accounting information systems utilization in SMEs in Banda Aceh City. The population in this study is all SMEs in Banda Aceh City. The sample was selected using purposive sampling, and the sample size was determined using the Slovin formula, resulting in 100 SMEs in the fashion business field in Banda Aceh City as a sample. The primary data is obtained through the distribution of questionnaires via online platforms such as WhatsApp, collected using Google Forms, and analyzed by multiple linear regression models. The findings of this study indicate that computer self-efficacy does not affect the effectiveness of utilizing an accounting information system. However, non-physical work environment, education level, and accounting knowledge affect the effectiveness of utilizing an accounting information system.